Agrimonolide and Desmethylagrimonolide Induced HO-1 Expression in HepG2 Cells through Nrf2-Transduction and p38 Inactivation - Chen, Lei; Teng, Hui; Zhang, Kalin Yanbo; Skalicka-Woźniak, Krystyna; Georgiev, Milen I.; Xiao, Jianbo (Frontiers in Pharmacology, 2017)
Agrimonolide and desmethylagrimonolide are the main bioactive polyphenols in agrimony with well-documented antioxidant, anti-diabetic and anti-inflammatory potential. We report here for the first time that agrimonolide and desmethylagrimonolide stimulate the expression of phase II detoxifying enzymes through the Nrf2-dependent signaling pathway. Agrimonolide and desmethylagrimonolide also possess considerable protective activity from oxidative DNA damage. In order to explore the cytoprotective potential of agrimonolide and desmethylagrimonolide on oxidative stress in liver, we developed an oxidative stress model in HepG2 cells, and check the hypothesis whether Nrf2 pathway is involved. Western blotting and luciferase assay revealed that exposure of HepG2 cells to agrimonolide or desmethylagrimonolide leads to increased heme oxygenase-1 (HO-1) expression by activating ARE through induction of Nrf2 and suppression of Kelch-like ECH-associated protein 1 (Keap1). Moreover, agrimonolide and desmethylagrimonolide also activated ERK signaling pathways and significantly attenuated individual p38 MAPK expression, subsequently leading to Nrf2 nuclear translocation. In conclusion, our results indicated that transcriptional activation of Nrf2/ARE is critical in agrimonolide and desmethylagrimonolide-mediated HO-1 induction, which can be regulated partially by the blockade of p38 MAPK signaling pathway and inhibiting nuclear translocation of Nrf2.